2022
DOI: 10.3389/fchem.2022.966332
|View full text |Cite
|
Sign up to set email alerts
|

Toward practical issues: Identification and mitigation of the impurity effect in glyme solvents on the reversibility of Mg plating/stripping in Mg batteries

Abstract: Reversible electrochemical magnesium plating/stripping processes are important for the development of high-energy-density Mg batteries based on Mg anodes. Ether glyme solutions such as monoglyme (G1), diglyme (G2), and triglyme (G3) with the MgTFSI2 salt are one of the conventional and commonly used electrolytes that can obtain the reversible behavior of Mg electrodes. However, the electrolyte cathodic efficiency is argued to be limited due to the enormous parasitic reductive decomposition and passivation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Therefore, our design strategy is to form glyme solvates of Mg 2+ within these HFE solvent environments to create electrolytes with minimal free glyme and minimal coordinated HFE populations (see Scheme ). Mg­(TFSI) 2 was selected as an initial salt candidate for this proof-of-concept due to its commercial availability, good solubility, high oxidative stability, and ability to support Mg cycling at moderate coulombic efficiency (CE) of up to approximately 80% even without Cl – additives. , Two HFE exemplars, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and bis­(2,2,2-trifluoroethyl)­ether (BTFE), were focused on based on their history of use in Li + electrolytes and their distinct structures leading to differences in solvating power . TTE contains F atoms directly adjacent to the ether oxygen (affecting coordination strength) while BTFE does not.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our design strategy is to form glyme solvates of Mg 2+ within these HFE solvent environments to create electrolytes with minimal free glyme and minimal coordinated HFE populations (see Scheme ). Mg­(TFSI) 2 was selected as an initial salt candidate for this proof-of-concept due to its commercial availability, good solubility, high oxidative stability, and ability to support Mg cycling at moderate coulombic efficiency (CE) of up to approximately 80% even without Cl – additives. , Two HFE exemplars, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and bis­(2,2,2-trifluoroethyl)­ether (BTFE), were focused on based on their history of use in Li + electrolytes and their distinct structures leading to differences in solvating power . TTE contains F atoms directly adjacent to the ether oxygen (affecting coordination strength) while BTFE does not.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to precipitated solid species, there is some evidence that TFSI − decomposition could result in products that are soluble in G2. A recent study on the effect of impurities in MIBs with glyme solvents by Yang et al 67 applied electrospray ionization mass spectroscopy (ESI-MS) to study electrolyte speciation. The authors observed several F-and Ncontaining species in the electrolyte; because these were seen only in the conditioned electrolytes, these species could come from only TFSI − decomposition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure C shows the expanded and deconvoluted C 1s spectrum before and after charge–discharge. Four deconvoluted peaks are observed at ∼284.2, ∼285.8, ∼286, and ∼290.8 eV before cycling, corresponding to C–C/C–H, Mg–C, C–O–C/CH 2 , and MgCO 3 /CO bonds, respectively. After the charge–discharge cycling, only three peaks are observed. No shift in the peaks at ∼284.2 eV (C–C/C-H) and ∼286 eV (C–O–C/CH 2 ) has been observed after cycling; however, the intensity of C–O–C/CH 2 peak increases substantially, and a slight decrease in the intensity of C–C/C-H peak has been noted.…”
Section: Resultsmentioning
confidence: 99%